2016
DOI: 10.3382/ps/pev356
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of the intestinal mucosa in Eimeria and E. Coli challenged broilers supplemented with amino acids

Abstract: The aim of this study was to evaluate the regeneration of the intestinal mucosa in Eimeria and E. coli challenged broilers supplemented with glutamine, arginine, and threonine. Six hundred male broilers at one d of age from the Cobb strain were utilized. The design was completely randomized using a 2×3 factorial design (unchallenged and challenged and 3 diets). A commercial diet was used as a control and 2 other diets were formulated with glutamine (1.5 and 3% Aminogut®), arginine (1 and 2% L-Arginine), and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 45 publications
0
14
0
4
Order By: Relevance
“…Previous studies showed that broilers challenged with Eimeria spp. have poor performance in part because of structural and functional changes that occur in the intestinal mucosa during the infection [5, 7, 8]. We observed that EC chickens had FI and BWG 13% and 37% lower than UC chickens, respectively.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Previous studies showed that broilers challenged with Eimeria spp. have poor performance in part because of structural and functional changes that occur in the intestinal mucosa during the infection [5, 7, 8]. We observed that EC chickens had FI and BWG 13% and 37% lower than UC chickens, respectively.…”
Section: Discussionmentioning
confidence: 86%
“…During the infection, the immune [1] and antioxidant systems are activated [2], and alterations in nutrient digestion and absorption occur [35]. Several studies reported that animals with coccidiosis show changes in intestinal morphology [6, 7], alterations in the expression of genes encoding digestive enzymes and transport proteins in the small intestine [5, 8], increased formation of reactive oxygen species (ROS) and reactive nitrogen species (RNS) [9], alterations in antioxidant enzyme activities [2, 10], and reduced concentrations of non-enzymatic antioxidants [11]. These changes are associated with poor animal performance, low efficiency, and increased mortality, causing global economic losses every year [12].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, amino acids are beneficial in improving the general physiological status(Bouyeh et al 2016), immunizing against infectious diseases(Faluyi et al 2015), and stabilizing under noninfectious or managemental conditions(Saleh et al 2018) thereby enhancing the production performance of birds(Ghoreyshi et al 2019). Previous studies showed that broilers challenged with any infection had poor performance because of structural and functional changes that occured in the intestinal mucosa during the infection (Su et al 2015;Gottardo et al 2016). Enteric infections in broilers may have a large influence on the endogenous amino acids losses within the gastrointestinal tract (GIT).…”
mentioning
confidence: 99%
“…For the goblet cell count, the cecum sections were analyzed under the microscope and the number of cells from ten random fields were counted, the marked goblet cells were accounted and from these values an average was obtained according to Gottardo et al (2016).…”
Section: Methodsmentioning
confidence: 99%